Electrode Impedance Fluctuations as a Biomarker for Inner Ear Pathology After Cochlear Implantation. Issue 10 (December 2017) - Choi, June; Payne, Matthew R.; Campbell, Luke J.; Bester, Christo W.; Newbold, Carrie; Eastwood, Hayden; O'Leary, Stephen J.
Abstract : Objectives/Hypothesis: Cochlear implant surgery now aims to preserve residual low frequency hearing. The current research explores whether fluctuations in the electrical impedance of cochlear implant electrodes may act as a biomarker for pathological changes that lead to the delayed loss of residual hearing. Study Design: Secondary analysis of a double-blinded randomized trial, where methylprednisolone was administered intravenously before cochlear implantation with a view to preserving residual hearing. Methods: Seventy-four patients with residual hearing after cochlear implant surgery were investigated for an impedance "spike, " defined as a median rise of ≥4 kΩ across all electrodes from the baseline measurements. Spikes were related to objective and subjective hearing loss, dizziness, and tinnitus. Results: An impedance spike occurred in 14% (10/74) of enrolled patients. Three months after surgery, five patients exhibited spikes and three of these patients had a total loss of their residual hearing. 4.3% of the 69 patients without spikes lost residual hearing. At 1 year, 9 of 10 patients who exhibited spikes had lost all their residual hearing. 8.1% of the 37 patients who did not experience a spike lost their residual hearing. Seventy percent of patients exhibiting a spike also experienced vertigo. The administration of steroids at the time of surgery did not influence the occurrence of spikes. Conclusion: Our results suggest that there is a relationship between a spike and the loss of residual hearing. It seems that rises in impedance can reflect pathology within the inner ear and predict the future loss of residual hearing. Abstract : Supplemental Digital Content is available in the text